Migration of Human Renal Tubular Epithelial Cells in Response to Physiological Electric Signals - Guan, Linbo; Fan, Ping; Liu, Xinghui; Liu, Rui; Liu, Yu; Bai, Huai (Frontiers in Cell and Developmental Biology, 2021)
Restoration of proximal tubular cell integrity and function after ischemic injury involves cell migration and proliferation. Endogenous fields are present during embryonic development and wound healing. Electric field (EF)-induced effects on cell migration have been observed in many cell types. This study investigated the effect of physiological direct current EF (dc EF) on the motility of renal epithelial cells. Human renal tubular epithelial (HK-2) cells were exposed to dc EF at physiological magnitude. Cell images were recorded and analyzed using an image analyzer. Cell lysates were used to detect protein expression by western blot. Scratch wounds were created in monolayers of HK-2 cells, and wound areas of cells were measured in response to EF exposure. Cells migrated significantly faster in the presence of an EF and toward the cathode. Application of an EF led to activation of the Erk1/2, p38 MAPK and Akt signaling pathways. Pharmacological inhibition of Erk1/2, p38 MAPK and Akt impaired EF-induced migratory responses, such as motility rate and directedness. In addition, exposure of the monolayers to EF enhanced EF-induced HK-2 wound healing. Our results suggest that EFs augment the rate of single renal epithelium migration and induce cell cathodal migration through activation of Erk1/2, p38 MAPK and Akt signaling. Moreover, exposure of the renal epithelium to EF facilitated closure of in vitro small wounds by enhancing cell migration.